Accumulation by urban dispossession: struggles over urban space in Accra, Ghana. Issue 1 (7th October 2015) - Gillespie, Tom
Abstract : This article draws on original empirical research in Accra, Ghana to explore the particular dynamics that contemporary processes of class‐based dispossession assume at the urban scale, posing the concept of 'accumulation by urban dispossession'. It responds to recent calls to shift the focus of urban theory from North to South and demonstrates how widely used concepts must be interrogated and reworked as they travel from place to place. Accra is home to a large informal proletariat that is excluded from formal wage labour and housing markets and therefore has to create urban commons in order to reproduce itself. Since these commons place limits to capital's ability to valorise the urban fabric, state‐led accumulation by urban dispossession is a strategic response that employs a range of physical‐legal and discursive mechanisms to overcome these limits through the enclosure of the urban commons and the expulsion of the informal poor. This argument problematises Harvey's capital‐centric theory of accumulation by dispossession, which treats enclosure as a fix for capital's inherent crisis tendencies. Furthermore, it demonstrates that primitive accumulation in this context differs from the classic form described by Marx on the grounds that it is based on the expulsion of the dispossessed rather than their incorporation into the capital relation as labour power.